Integrated Expert Systems and Videodisc in Surgical Pathology: An Overview - Nathwani, B.; Heckerman, David; Horvitz, Eric; Lincoln, T. (Human Pathology, 1990)
We present an overview of our 6-year experience in the design of expert systems for anatomic pathology. Our practical goal is to help practicing pathologists with learning, teaching, and the task of diagnosis by providing them with dynamic expert knowledge by means of a personal computer. This project could only be undertaken by first addressing a scientific goal: to characterize the problem-solving strategies that expert pathologists use in making a diagnosis and to state them in the logical terms of computer science. Our approach has been to build systems first for experimentation and then for use. The result of our work is an integrated computer-based approach that handles expert knowledge as formal relationships and morphologic images and that uses a number of logical strategies to provide multiple perspectives on diagnostic tasks. Configured as a pathologist's workstation, this approach can be expected to enhance the performance of trained general pathologists and pathologists in training. Lymph node pathology has been used as the prototype domain for this research, but care has been taken to seek a generalized authoring and inference structure that can be applied to other areas of pathology by changing the contents but not the structure itself. Excursions into various surgical pathology specialties suggest that the ways the system is constructed and exercised is fundamentally robust. Such computer-based expert systems can be expected to generate a new standard in the practice of pathology–based on the "gold standard" of classical morphology, but including the coordinated use of new methods from immunology and molecular biology in a multidisciplinary approach to diagnosis when these techniques are relevant. The benefits from this technology can be expected to be widespread with the evolution, refinement, and diffusion of these systems.